Trends in hemodialysis-related search interest in Indonesia: a decade Google Trends analysis - Iryawati, Dinda; Efiyanti, Christy; Yurianingsih; Fadlurrahman Zuhair, Chandra; Manggala Putra, Mochamad; Wahyu Aryanto, Nur Jaelani; Nurlaela, Desi (UNUSA Press, 2025)
Background: Despite the rising burden of end-stage renal disease (ESRD) and the rapid expansion of hemodialysis services, there is limited research exploring how Indonesians seek information about this topic online. Understanding digital health-seeking behavior is crucial for improving public education and access to care. Methods: This study analyzes public interest in hemodialysis in Indonesia over a decade (2014–2024) using Google Trends data. Several hemodialysis-related keywords were examined, including both lay and clinical terms. Search trends were evaluated over time and across provinces, and related search queries were also assessed. Results: The results show a steady increase in search volume for hemodialysis-related terms, with “cuci darah” consistently dominating over clinical terms such as “hemodialisa,” “hemodialisis,” and “hemodialysis.” Regional analysis reveals higher relative search interest in certain provinces, indicating potential geographic disparities in awareness or access to services. Common related search queries, such as “hemodialisa adalah” and “gagal ginjal,” reflect both curiosity about the procedure and broader concerns about kidney health. Conclusion: These findings suggest that online health-seeking behavior in Indonesia is growing, but also highlight gaps in public knowledge. Monitoring digital interest through platforms like Google Trends may serve as a valuable tool to guide targeted public education, optimize kidney health communication strategies, and inform more responsive service planning. Given the persistent public preference for lay terminology, future health campaigns should consider integrating colloquial language such as